ANALYSIS OF CHESS PLAYING SKILLS ON MATHEMATICS LEARNING OUTCOMES JUNIOR ATHLETES RAJA KOMBI TRENGGALEK CHESS CLUB - Andika Yogi Setiawan; Henri Gunawan Pratama (Universitas Sebelas Maret, 2021)
This study aims to determine the results of the analysis of chess playing skills on mathematics learning outcomes for junior athletes of the Raja Kombi Trenggalek chess club. The research method used is a qualitative descriptive method with a quantitative approach. Participants in this study were 8 junior athletes of Raja Kombi Trenggalek chess club. Data collection techniques using interviews, skills results and documentation. The data analysis in this study used the mean and percentage formula. After analyzing the data, the results of this study concluded that in this study, the average score of playing chess skills was 85.00, then the average score of mathematics learning outcomes was 86.25. This is of course the higher the level of achievement of skills or intellectual intelligence, the higher the level of problem solving such as in learning mathematics. This is also influenced by motor and psychological aspects as a support for intelligence skills that affect the thinking of athletes. Then from the data analysis it can be said that the higher the level of achievement of chess playing skills, the higher the level of problem solving as in learning mathematics